Income Distribution and Aggregate Saving: Theory and China's Evidence. Issue 2 (1st February 2017) - Chen, Yi; Kong, Lu; Wang, Rui; Hu, Jiamin
ABSTRACT: Using a parsimonious heterogeneous-agent general equilibrium model, this study reveals a positive causal effect of income inequality on the aggregate saving rate. In the model economy, benevolent individuals save to leave offspring bequests. Since bequests are luxury, the rich have a higher marginal propensity to save. Then, else equal, a fall in income inequality will lower the economy-wide saving rate. The model predicts an augmented aggregate saving function: the aggregate saving rate depends positively not only on the aggregate income level, but also on the dispersion of income. We find some empirical support for this hypothesis using China's province-level longitudinal data.